Question 1 \( 1 \cdot 1 \frac{9^{x}+3^{2 x+1}}{18^{x} \cdot 2^{-x}} \)
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Extra Insights
To simplify the expression \( 1 \cdot 1 \frac{9^{x}+3^{2 x+1}}{18^{x} \cdot 2^{-x}} \), we start by rewriting the components: 1. Notice that \( 9^{x} = (3^2)^{x} = 3^{2x} \), and hence the expression in the numerator becomes \( 3^{2x} + 3^{2x+1} = 3^{2x}(1 + 3) = 4 \cdot 3^{2x} \). 2. In the denominator, \( 18^{x} = (2 \cdot 3^2)^{x} = 2^{x} \cdot 3^{2x} \). Since we also have \( 2^{-x} \), we can rewrite \( 18^{x} \cdot 2^{-x} \) as \( 2^{x} \cdot 3^{2x} \cdot 2^{-x} = 3^{2x} \). Now substituting these back into the simplified expression, we have: \[ \frac{4 \cdot 3^{2x}}{3^{2x}} = 4 \] Thus, the simplified answer is \( 4 \).